The Limitations of Yoruba-English Bilingual Undergraduate Students in the Expression of Yoruba Greetings - Adegbite, Wale; Akinwale, Layi (Linguistic Association of Nigeria, 2014)
This study investigated the limited ability of some Yoruba-English speakers to express Yoruba greetings in either Yoruba or English. The responses of 120 Yoruba-English bilingual undergraduate students in a Nigerian university were elicited via the questionnaire and interview techniques and then analysed to determine, first, the strategies employed by the students in the expression of greetings and, second, their levels of competence in expressing greetings in both languages. The findings revealed that the students expressed the greetings via specific or general (socially acceptable), individual non-acceptable, and silence (no response) forms in both Yoruba and English; and that they found it more problematic to express greetings in English than in Yoruba. It was concluded that the non-expression of greetings as well as inability to express greetings appropriately is fast becoming a habit among the youths and that education and enlightenment efforts should be made to reverse this retrogressive trend.